WHAT MAKES TEACHERS DEVELOP PROFESSIONALLY: SOME REFLECTIONS ON MOTIVATIONAL ISSUES IN THE CONTEXT OF POST-GRADUATE STUDY PROGRAMMES - Droździał-Szelest, Krystyna (Neofilolog, 2019)
This article explores the concept of teacher professionalism, focusing primarily on factors motivating teachers to pursue professional development within the framework of formal, organized teacher development programmes offered by educational institutions. Its major purpose is to contribute to a better understanding of motivational issues involved in teacher education, or teacher learning, as it is sometimes referred to. Its other purpose is to liven up a discussion concerning language teacher education as a life-long experience. The article consists of two parts: its theoretical sections focus on the notions of professionalism and a professional, together with the concepts of autonomy and reflection/reflective practice, which are crucial from the point of view of teacher development. Next, factors motivating teachers to continue their development both as professionals and as individuals are addressed. The second part present and discusses results of a small-scale individual research project which yielded some interesting data pertaining to motivational issues involved in teacher learning.